Chemistry matters cge'o' level 2nd edition - Toon, Tan Yin; Kwong, Chen Ling Sadler, John (Marshall Cavendish; Singapore)
from a review: "Chemistry Matters textbook is written in alignment with the latest GCE Ordinary Level Chemistry syllabus by the Ministry of Education, Singapore. ... Makes Chemistry engaging, clear and simple - Captivating chapter openers with attractive photos and though-provoking questions spark off the inquiry process. - Concepts presented within authentic contexts make Physics relevant, useful and interesting. - Step-wise presentations with infographics and flow charts break down difficult concepts into easy-to-understand bites. - Illustrations and photographs and visualisation of abstract concepts. Links to online animations and videos provides dynamic visual learning support. Promotes learning with understanding and hones critical thinking - Hands-on activities enable the experiential learning that strengthens conceptual understanding. - Links between chapters and end-of-chapter concept maps highlight interconnected concepts. - Worked examples guide students on how to apply concepts. - Regular test questions prompt immediate checks on understanding, providing opportunities for assessment for learning. - Ample practice questions, including challenging and data-based questions, nurture higher-order thinking skills and agile minds that are able to apply concepts on novel situations. Develops 21st century competencies - A diagnostic checklist for every chapter surfaces flaws in conceptual understanding and promotes self-directed learning by guiding students to the relevant sections for revision. - Group and online learning activities that require students to evaluate, process and communicate information, foster independent learning, problem-solving, ICT, interpersonal and collaborative skills. Above extract from Preface of Chemistry Matters Textbook